Uterine myoma: еtiology and morphogenesis - Н. В. Косей (Publishing House TRILIST, 2018)
Uterine myoma is the most common tumor of female genital organs. Despite the significant achievements of modern science and the many studies devoted to this benign tumor, its initiating factors remain unknown. To investigate etiological factors and features of the morphogenesis of uterine leiomyoma for further development of the tactics of its prevention and treatment, the literature data and the results of our original studies, including results of submicroscopic studies, were analyzed. It was revealed that among important etiological factors are African-American ethnic group, nutrition rich in meat, high blood pressure, age, inflammation and stress. Different clinical and pathogenetic variants of development of uterine myomas have been identified: isolated and combined with dyshormonal diseases of the mammary glands. At the ultrastructural level, the development of isolated uterine myoma was accompanied by significant changes in the organelles of a degenerative-destructive nature along with significant pericellular fibrosis, while the combined variant of uterine leiomyoma was characterized by activation of nuclear structures and an increase in the number of energy and plastic organelles, which indicates intensification of metabolic processes in them and an increase in the proliferative potential. It was shown that the tumor develops from a single stem cell of the myometrium and grows, moving aside normal uterine tissues and creating around itself pseudocapsule - a site of compressed myometrium at the border of healthy tissue and fibroids, rich in collagen fibers, neurofibrils and blood vessels, which provides regeneration and restoration of myometrium functionality after myomectomy. The frequency of recurrence of the tumor is significantly higher in the presence of multiple myomas, which should be taken into account when planning conservative myomectomy. When planning the treatment of uterine leiomyoma, it is also necessary to take into account the clinical and pathogenetic variant of its development. In the presence of an isolated variant, the first stage is necessary to perform anti-inflammatory therapy and correction of local factors, after which it is possible to perform specific treatment for fibroids, and in combination with other dyshormonal pathology - first of all to correct systemic disorders and then plan the treatment of fibroids.